Sosialisasi Sistem Informasi Pencatatan Keuangan Berbasis Digital bagi Pelaku UKM di Desa Wonreli Pulau Kisar Kabupaten Maluku Barat Daya - Litualy, Janet Wilsye; Leunupun, Engrith Grafelia (Pelita: Jurnal Pengabdian kepada Masyarakat, 2023)
In running a business, the success of SMEs is inseparable from the ability to manage business funds. Mistakes in managing funds can threaten the sustainability of SMEs. With good fund management, UKM can detect, prevent and make corrections to the recording of transactions that have been carried out by UKM. Clear accounting information can be obtained by preparing financial reports. For this reason, in an effort to arouse the enthusiasm of UKM players and at the same time to support government programs to create quality entrepreneurs who are able to compete in the Digital Era 4.0, the PSDKU Unpatti accounting lecturer team in Southwest Maluku Regency took the initiative to carry out community service by making activities in the form of system socialization digital-based financial recording information for SMEs in Wonreli Village, Kisar Island, Southwest Maluku Regency. This program is intended so that participants understand SMEs in the Digital Age and have more insight and ability to carry out financial reporting using a digital-based recording information system.